The Importance of MILD Combustion, Biogas and The Impact on The Global Warming - Muhamad, Mat Noor (2020)
The energy demand is dramatically increasing due to the growth of the world's population and substantial economic development in Brazil, Russia, China, and India. The combustion of fossil fuel is projected to fulfil about 75% of this energy needs. Some of the significant challenges are to provide efficient energy and limit greenhouse gas (GHG) emissions. Combustion pollution will increase the earth's temperature, create unstable weather, increase ocean levels, and ice melting in the North and South Poles.